Assessing the Efficacy of Coding with Scratch and AI Interaction Using ChatGPT on 5th Graders’ Math Performance and Computational Thinking - Febriantoro, Firdaus Suryo; Fatharani, Atika; Dewi, Nurlita Candra; Kurniati, Lenny (Universitas Islam Lamongan, 2025)
This study explores the effectiveness of integrating coding using Scratch and AI interaction via ChatGPT to enhance the mathematics performance and computational thinking skills of 5th-grade students. An experimental group, which received training using these tools, showed significant improvements in mathematical problem formulation, data organization, and higher-order cognitive skills such as analysis, evaluation, and creation, as measured by Bloom's Taxonomy. These gains were notably higher compared to a control group using traditional methods. The results demonstrate that the use of Scratch for coding and ChatGPT for AI interaction not only enhances mathematical understanding but also fosters critical thinking, problem-solving, and collaborative learning. This integration supports the development of computational thinking, preparing students for future challenges in a technology-driven world. The study highlights the potential of digital tools in transforming primary education by promoting deeper engagement and fostering essential 21st-century skills.